Analisis Implementasi Mitigasi Perubahan Iklim dalam Paris Agreement: Studi Perbandingan di Asia-Pasifik - Malika Rinda Rachmawati; Nur Gemilang Mahardhika (Prosiding Seminar Hukum Aktual Fakultas Hukum Universitas Islam Indonesia, 2025)
Abstract As a form of commitment to the problem of climate change through the Paris Agreement, the heads of state in the world have formed their respective NDCs and LT-LEDS. Indonesia, Malaysia, Singapore, Australia and New Zealand are countries in the Asia-Pacific region that have signed the Paris Agreement and are committed to reducing global GHG emissions. On this basis, this study discusses the commitment of the five countries in implementing climate change mitigation according to the Paris Agreement through the NDC and LT-LEDS documents. This study will answer the challenges of implementing climate change mitigation in the five Asia-Pacific countries and the successes and challenges faced in these mitigation efforts. The normative legal method was chosen for this research with a regulatory, contextual and comparative approach. The study results show variations in strategies, achievements and levels of ambition for reducing emissions in the five countries. In general, the use of renewable energy is the main mitigation strategy in this region, the success of which depends on policy and investment factors.